Efektivitas Role Playing Dalam Pembelajaran Pai Untuk Meningkatkan Partisipasi Siswa Kelas XI-IPA - Tsabitah, Sultan; Harfiani, Rizka (EL-EMIR Institute, 2025)
This study was motivated by the low level of student engagement in Islamic Religious Education (PAI) classes. Initial observations indicated that many students remained passive, reluctant to voice their opinions, and showed limited involvement during lessons. To overcome this challenge, the role-playing method was employed as an alternative learning strategy that offers greater interaction and enjoyment. The research applied a Classroom Action Research (CAR) design carried out over two cycles with 27 students of grade XI-IPA in the odd semester of the 2025/2026 academic year. Data were obtained through achievement tests, observation sheets of student activity, field notes, and documentation. The findings revealed that the use of the role-playing method significantly enhanced student participation in PAI learning. This increased participation also contributed to better learning mastery, self-confidence, and discipline. Therefore, the role-playing approach is recommended to foster a more active, meaningful, and engaging classroom environment.